Uganka protonskega radija - Rihtaršič, Gregor (Matrika, 2020)
This article deals with discrepancies between measurements of the proton charge radius which gained their reputation over the past decade under the nickname "proton radius puzzle". Firstly the elastic electron-proton scattering measurements are discussed with emphasis on the experiment at the Mainz Microtron. After that the results of the reanalysis of the data from Mainz are presented yielding charge radius values of ?$(0.876 ± 0.006)$? fm and ?$(0.868 ± 0.048)$? fm which coincide with the larger proton radius. Then, Lamb shift measurements are explained and a short overview of the latest experiments which may foreshadow the solution of the puzzle is provided. At the end the impact of the puzzle on nuclear and atomic physics is discussed.
Keywords: charge radius; elastic scattering; elastično sipanje; jedrska fizika; nabojni radij; nuclear physics; proton